The Frequency of Cytochrome P450 2E1 Polymorphisms in Black South Africans - Chelule, Paul K. (IOS Press, 2006)
Polymorphisms in the promoter region of the Cytochrome P4502E1 (CYP2E1) gene reportedly modify the metabolic activity of CYP2E1 enzyme, and have been associated with increased susceptibility to squamous cell carcinoma (SCC) of the oesophagus in high prevalence areas such as China. To assess the frequency of these polymorphisms in Black South Africans, a population with a high incidence of oesophageal SCC, this study examined genomic DNA from 331 subjects for restriction fragment length polymorphisms in the CYP2E1 (RsaI and PstI digestion). The frequency of the CYP2E1 c1/c1 and c1/c3 genotypes was 95% and 5% respectively. The frequency of the CYP2E1 allele distribution was found to be markedly different between Chinese and South African populations; hence it is important to place racial differences into consideration when proposing allelic variants as genetic markers for cancer.